2015
DOI: 10.1002/apj.1947
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally investigation of the effects of nanoparticles‐enriched ASP formulations on the spontaneous imbibition in a fractured sandstone reservoir

Abstract: Among the chemical methods used in oil industry to boost the ultimate oil recovery, ASP (alkaline surfactant polymer) flooding has gained much attention because of beneficial effects related to simultaneous usage of three different chemical agents. This study is devoted to investigate the separate influences of each chemical agent in the ASP on the attained oil recovery. Furthermore, four different ASP formulations are prepared, and effects of hydrophilic nanoparticles are examined on the ASP spontaneous imbib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Recently, several authors have reported the use of nanotechnology in synergy with different conventional EOR techniques such as polymer flooding, surfactant flooding, , and alkali–surfactant–polymer flooding , to increase its performance regarding areal sweep efficiency, wettability alteration, and interfacial tension for improving oil recovery. In this sense, Xu et al focused their work on the formulation of a nanofluid based on an anionic surfactant and commercial silica gel nanoparticles for obtaining ultra-low interfacial tension.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several authors have reported the use of nanotechnology in synergy with different conventional EOR techniques such as polymer flooding, surfactant flooding, , and alkali–surfactant–polymer flooding , to increase its performance regarding areal sweep efficiency, wettability alteration, and interfacial tension for improving oil recovery. In this sense, Xu et al focused their work on the formulation of a nanofluid based on an anionic surfactant and commercial silica gel nanoparticles for obtaining ultra-low interfacial tension.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results related to the water-flooding process on the reservoir formation plugs are obtained by the displacement equipment described above. Produced oil from the core is monitored in all water-flooding processes, and recovery data are plotted against injected pore volume as a function of dimensionless time using the following formula: 48,49…”
Section: ■ Experimental Outcomesmentioning
confidence: 99%
“…The experimental results related to the water-flooding process on the reservoir formation plugs are obtained by the displacement equipment described above. Produced oil from the core is monitored in all water-flooding processes, and recovery data are plotted against injected pore volume as a function of dimensionless time using the following formula: , where t D is dimensionless time, σ is interfacial tension, k absolute permeability, ϕ porosity, μ w , μ o water and oil viscosity, and L is a core length. For the wettability effect, the experimental method used to evaluate the rock wettability is the Amott method, which consists of carrying out two types of displacements on a sample: a natural displacement created by the capillary phenomena, called spontaneous displacement, and a forced displacement under a pressure using a centrifuge or a Hassler device, called mechanical displacement.…”
Section: Experimental Outcomesmentioning
confidence: 99%